Analisis Strategi Pemasaran Usaha Mikro Kecil dan Menengah (UMKM) pada Era Digital di Kota Medan - Rizky Ananda Ariza; Nuri Aslami (LPPM IAI Nasional Laa Roiba Bogor, 2021)
Because of the rise of technology and increased business competition, SMEs must have a strong and well-defined marketing plan in order to succeed. The goal of this study is to look at how marketing strategies are implemented in SMEs in order to compete in the digital age. The researchers used a qualitative technique in this study, conducting structured interviews with the owners or top management of SMEs, with a total sample size of 31 respondents. The findings of this study revealed that the culinary, fashion, and tour and travel industries use added value and differentiation strategies for their products and services, as well as a competitive pricing approach. In the trading industry, on the other hand, they are more likely to employ a price strategy to compete in the market and to select a niche market to develop their target market. Keywoard : Marketing Strategy, Marketing Mix, SMEs, Medan